Urinary Tract Infection, Incidence, Uropathogens and Antibiotic Sensitivity in Females - Mahaseth, Binod Kumar; Verma, Pramod; Malla, Tark (Journal of Nepalgunj Medical College, 2017)
Introduction: Urinary tract infection in female population is one of the most common clinical infectious pathologies found worldwide due to anatomical location of urethral opening in relation to males. Continuous assessment of uropathogens and their sensitiveness to chemotherapeutic agent help us to manage these. The aim of this study to determine the presence of uropathpgens and their sensitkng from UTI. Method: It is a hospital based cross sectional study conducted at NGMC Teaching Hospital Kohalpur from July 2016 to June 2017. The urine samples were collected using the mid-stream clean catch method from 948 clinically suspected UTI female patients and the irantibiotic sensitiveness was determined using the standard procedures. Result: Overall culture positive was found in 262 patients (27.6%) among 948 urine samples. Among them e. coli contributed to cases 179(68.3%) followed by klebsiella 38(14.5%), enterobacter 21(8%), fungal 10(3.9%).Maximum no. of uropathogens were sensitive to chloramphenicol 224(93.4%) followed by nitrofurantin 232(88.7%), amikacin 246(94%), tobramycin 241(92.8%) and gentamycin 229(85.5%). Most of the organism were found to be resistant with ampicillin 255(97.5%) followed by cefpodoxime 242(92.4%), vancomycin 235(90%) and amoxicillin 234(89.6). Conclusion: and recommendation – Chloramphenicol, Nitrofurantin, Amikacin, Gentamicin and Tobramycinare the drugs of choice for the empirical therapytill the culture and sensitivity report is available. Continuous assessment is required for the early diagnosis and management of UTI.The culture and the sensitiveness of uropathogen are to be done and the treatment should be modified accordingly.